Kemudahan dan perkhidmatan maklumat di Kolej bersekutu uitm: satu kajian - Che Daud, Suriana; Akmar Hj. Ismail, Saidatul; Hj Ibrahim, Zohra; Abdul Rahim, Hasnah (Persatuan Pustakawan Malaysia, 2010)

(untitled)
Libraries in universities and university colleges are there to serve their users in their quest for information. Various information services and facilities are provided to satisfy their users’ needs. This study looks at facilities and services provided by the libraries in five UiTM affiliated colleges within the Klang Valley. The qualitative study looks at eleven areas and the results are benchmarked against Persatuan Pustakawan Malaysia’s guidelines for college libraries.